Pacemaker versus defibrillator therapy in patients eligible for cardiac resynchronisation therapy: evidence from the German Device Registry - Lange, Philipp Sebastian; Frommeyer, Gerrit; Kleemann, Thomas; Brachmann, Johannes; Lugenbiel, Patrick; Reif, Sebastian; Hochadel, Matthias; Senges, Jochen; Eckardt, Lars (Journal of Clinical Medicine, 2025)
Background: According to current guidelines, cardiac resynchronisation therapy (CRT) is recommended in patients with significantly impaired left ventricular systolic function and left bundle branch block. However, the decision between pacemaker (CRT-P) and defibrillator (CRT-D) in patients eligible for CRT remains a matter of debate. Register data have shown a higher all-cause mortality in CRT-P in comparison to patients with a CRT-D. Here, we investigated clinical determinants of the selection of CRT-P vs. CRT-D and clinical outcome in large registry data from a multi-centre ‘real-life’ registry on patients with CRT defibrillator or pacemaker therapy. Methods: The German Device Registry (DEVICE) is a nationwide, prospective registry with one-year follow-up investigating 5451 patients receiving device implantations in 50 German centres. The present analysis of DEVICE focused on all patients from the register receiving cardiac resynchronization therapy. Results: Out of 1603 patients receiving cardiac resynchronisation therapy, 1536 (95.8%) received a CRT defibrillator system and 67 (4.2%) a CRT pacemaker system. Patients in the CRT-P group had a significantly better left ventricular systolic function compared to the CRT-D group (median 35% vs. 25%), and significantly less often had a history of myocardial infarction (9.0% vs. 25.2%). A preexisting pacemaker and a history of stroke/peripheral embolism were identified as determinants for the selection of CRT-P vs. CRT-D. Overall mortality after one-year follow-up was 8.0%. Patients with ischemic cardiomyopathy receiving CRT-P therapy had a higher one-year mortality than patients receiving CRT-D (21.2% vs. 8.9%, p = 0.020). On the other hand, patients with non-ischemic cardiomyopathy did not display differences between these two treatment groups (CRT-P 8.1%, CRT-D 6.6%, p = 0.72). Conclusions: Data from the German device registry show that most patients receiving cardiac synchronization therapy have an implanted CRT-D system. In comparison to patients with CRT-D, those with CRT-P more often had a non-ischemic cardiomyopathy and a preexisting pacemaker system. The outcomes between these two treatment groups were different as regards ischemic cardiomyopathy only.
Gesehen am 23.10.2025